Lifestyle risk factors of non-communicable diseases among patients after liver transplantation – a pilot study - Jagielska, Anna; Jankowski, Krzysztof; Okręglicka, Katarzyna; Skupin, Paulina; Kozłowska, Aleksandra; Durlik, Magdalena; Pruszczyk, Piotr; Nitsch-Osuch, Aneta; Tronina, Olga (Family Medicine & Primary Care Review, 2017)
Background . Liver transplantation (LT x) is the ultimate treatment for some hepatologic patients (pts), very often observed having excessive weight gain after operation, resulting in an increased risk of non-communicable diseases (NCD s). Objectives . The aim of the pilot study was to evaluate the chosen lifestyle risk factors of NCD s (nutritional status, intake of energy, micronutrients, cholesterol and fiber, smoking habit and physical activity) of LT x pts. Material and methods . The pilot study group consisted of 44 pts (13 women and 31 men) of the Department of Transplant Medicine and Nephrology, Medical University of Warsaw. Anthropometric, nutritional, smoking habit and physical activity data was collected from September 2015 till May 2016. Results . Mean body weight was 85.3 ± 15.6 kg, mean body mass index (BMI) – 29.1 ± 4.5 kg/m2, mean waist circumference (WC ) – 101.9 ± 12.3 cm, mean % of total body fat – 28.8 ± 7.9%. Only ca. 16% of pts had a normal BMI. More than 90% of pts had abdominal obesity. Mean energy intake was 1,605.4 ± 441.6 kcal (percentage of energy protein/total fat/carbohydrates – 18.2 ± 3.2%/34.4 ± 5.8%/47.1 ± 6.0%), cholesterol intake 264.6 ± 100.7 mg, dietary fiber intake 17.4 ± 5.8 g daily. Mean number of steps was 7,163.2 ± 3,344.5 per day, and mean daily MET was only 1.5 ± 0.3. Moderate physical activity lasted on average for 02:06 ± 01:27 (hh:mm). The prevalence for smoking was 23%. Conclusions . The diet of LT x pts was based on improper proportions of macronutrients. Anthropometric measurements of these patients revealed an impaired nutritional status, including metabolic obesity. The physical level of activity was insufficient. The prevalence for smoking was similar to the general Polish population. The presence of NCD risk factors among LT x pts requires the creation of interprofessional teams of health care workers.